TI-BEARING INTRUSIONS WITHIN PROTEROZOIC ANORTHOSITE COMPLEXES - MYTROKHINA, T.; MYTROKHYN, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The comparative characteristic of Ti-bearing intrusions within the most typical proterozoic anorthosite complexes is performed in the article. It is revealed, that the Korosten complex intrusions of the Ukrainian Shield, the Rogaland complex intrusions of the Baltic Shield and the Havre-Saint-Pierre complex intrusions of the Canadian Shield belong to different petrographic associations. The Korosten complex belong to anorogenic rapakivi granite-anorthosite association. The Rogaland complex and Havre-Saint-Pierre complex are parts of orogenic anorthosite-mangerite-charnocite-granite association. The conclusions about influence of geodynamic conditions on the main mechanisms of Fe-Ti oxide mineral concentration and also on the localization of ore bodies, their mode of occurrence, textural features and composition are made.